2010
DOI: 10.1007/s11426-010-4062-4
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic and mesoionic liquids: Molecular aggregation in 3-methylsydnone

Abstract: Ionic liquids are green solvents with interesting properties: displaying low melting points and high boiling points. They offer a new approach applicable in many instances. Nevertheless, the presence of free ions can be a matter in some cases, e.g. for the study of nucleophilic reactions, in electrochemistry, and in each situation where there is a competition between counter ions, as in micellization of ionic surfactants. Neutral compounds having formal unit electrical charges of opposite sign, and the same ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…There have been a number of non-aqueous molecular polar solvents which have been reported as amphiphile selfassembly solvents. These include the small glycol solvents of glycerol, [1][2][3][4] ethylene glycol, 1,5,6 1,3-propanediol, 2 1,2-propanediol, 2 1,4-butanediol, 2 1,3-butanediol, 2 small amides consisting of formamide, 1-4,6-15 N-methylformamide, 4,15 N-methylacetamide, 7 N,N-dimethylformamide, 2,4,6-8,15 N-ethylformamide, 15 N-pentylformamide, 15 N-(2-hydroxyethyl)acetamide, 15 N-tetrabutylformamide, 15 N,N-diethylacetamide, 15 and other solvents including hydrazine, 7,8 N-methylsydnone, 16,17 dimethyl sulfoxide, 6,7 formic acid, 2 2-aminoethanol, 2 1-amino-2-propanol, 2 2-mercaptoethanol, 2 ethylene diamine 2 and acetonitrile. 6 In addition to the molecular solvents it has been well established that many ionic liquids and molten salts share this ability.…”
Section: Ionic Liquids As Amphiphile Self-assembly Mediamentioning
confidence: 99%
See 3 more Smart Citations
“…There have been a number of non-aqueous molecular polar solvents which have been reported as amphiphile selfassembly solvents. These include the small glycol solvents of glycerol, [1][2][3][4] ethylene glycol, 1,5,6 1,3-propanediol, 2 1,2-propanediol, 2 1,4-butanediol, 2 1,3-butanediol, 2 small amides consisting of formamide, 1-4,6-15 N-methylformamide, 4,15 N-methylacetamide, 7 N,N-dimethylformamide, 2,4,6-8,15 N-ethylformamide, 15 N-pentylformamide, 15 N-(2-hydroxyethyl)acetamide, 15 N-tetrabutylformamide, 15 N,N-diethylacetamide, 15 and other solvents including hydrazine, 7,8 N-methylsydnone, 16,17 dimethyl sulfoxide, 6,7 formic acid, 2 2-aminoethanol, 2 1-amino-2-propanol, 2 2-mercaptoethanol, 2 ethylene diamine 2 and acetonitrile. 6 In addition to the molecular solvents it has been well established that many ionic liquids and molten salts share this ability.…”
Section: Ionic Liquids As Amphiphile Self-assembly Mediamentioning
confidence: 99%
“…However, since then 3-methylsydnone has been shown to have self-assembly ability and hence a network of hydrogen bonding is not a requisite property. 16,17 Cassel et al reported on the self-assembly in the aprotic 3-methylsydnone and commented that the discrepancy between studies is due to the Krafft temperature being solvent and surfactant dependent, and hence higher temperatures were required to observe amphiphile self-assembly in 3-methylsydnone. 17 It has been suggested that in aprotic ionic liquids there is an ionic network, instead of a hydrogen bonded network, and thus they are still structured around surfactant alkyl chains.…”
Section: Solvent Cohesionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 The requirement for solvent hydrogen bonding has been challenged more recently through reports of amphiphile self-assembly in for example 3-methylsydnone. 26,32,33 In amphiphile-solvent systems, lyotropic mesophases can include lamellar, and normal and inverse micellar, hexagonal, and discrete and bicontinuous cubic structures. Lamellar, hexagonal and cubic mesophases are ordered with one-, two-and three-dimensional periodicity, respectively.…”
Section: Introductionmentioning
confidence: 99%